Enhancing Counterterrorism Cooperation Through Intelligence Collaborations in Indomalphi (2018-2023) - Mutia Kartika Andalus; Muradi; Yusa Djuyandi (JURNAL KEAMANAN NASIONAL, 2023)
Terrorism issues are rapidly evolving in the Southeast Asian region, particularly for Indonesia, Malaysia, and the Philippines as countries directly impacted by terrorism issues due to the presence and growth of terrorist groups like Jamaah Islamiyah (JI) and Abu Sayyaf Group (ASG). Criminal activities and terrorism continue to occur in these three countries. Therefore, the Trilateral Cooperation Agreement (TCA) of Indomalphi collaboration was established in response to address terrorism issues that could threaten regional security and stability. One form of this cooperation is sharing intelligence information to detect the movements of terrorist groups. However, there are some obstacles in the implementation of cooperation in the Southeast Asian region, including distrust, the ASEAN Way, and differences in the paradigms of handling terrorism issues within Indomalphi. Hence, this article aims to analyze how the collaborative efforts by Intelkam Polri strengthen intelligence cooperation within Indomalphi on terrorism issues from 2018 to 2022. This paper employs a qualitative method with a theoretical approach. Primary data is obtained through documentation studies, and secondary data is obtained through literature review. The research findings indicate that Intelkam Polri has made collaborative efforts to strengthen intelligence cooperation within Indomalphi. This is evident through information sharing, workshops, training, and coordination with BAIS TNI and other cooperation units in Malaysia and the Philippines. However, operational aspects, as well as the determination of authority, responsibilities, and rights, should be clarified and articulated in a regulation or standard operating procedure (SOP) to facilitate Intelkam and cooperating units.